Clinical Management and Surgical Outcomes of Wandering Spleen with Splenic Torsion in Pediatric Patients: A Case Report - Memeti, Shaban; Kuci, Saimir; Risteski, Toni; Lazar Todorovic; Kamilovski, Marijan; Krsteska, Blagica; Sulejmani, Haris (Albanian Society for Trauma and Emergency Surgery, 2025)
Introduction: Wandering Spleen is a rare condition in which the splenic ligaments are abnormally loose or absent. This makes the Spleen more mobile and increases the risk of torsion. This case report outlines the clinical presentation and management of a 10-year-old female patient who presented at our clinic with acute abdominal pain, vomiting episodes, and a severe fever. Imaging tests, such as abdominal ultrasonography and computed tomography, confirmed the diagnosis of splenic torsion by showing a hemorrhagic infarction and a large spleen. We performed a splenectomy to remove the damaged organ, a partial omental resection to remove the dead tissue and removed the mesenteric lymph nodes for further pathological examination. After the surgical procedure, the intensive care unit carefully observed the patient and treated her with intravenous electrolyte replacement, broad-spectrum antibiotics, pain management, and measures to prevent thrombosis. This case highlights the critical need for early diagnosis and timely surgical intervention in cases of wandering Spleen to prevent serious complications, including splenic infarction. By presenting this case, we seek to elevate awareness of wandering Spleen among healthcare professionals, mainly within pediatric groups. We emphasize the importance of timely diagnosis and appropriate management to optimize patient outcomes. Conclusion: Early detection and prompt intervention are crucial in preventing severe complications in pediatric patients. This case emphasizes the necessity of rapid diagnosis and increased awareness in clinical practice. Due to the Spleen's impaired viability, a splenectomy was required. Following surgery, we provided comprehensive monitoring and pharmaceutical assistance to control pain, prevent infection, and maintain nutritional stability.
Keywords: Wandering spleen; splenic torsion; pediatric surgery; splenectomy; acute abdomen